Pengaruh 3 Kecerdasan Auditor Terhadap Ketepatan Pemberian Opini Dengan Pengalaman Sebagai Moderasi - Yunita Kurnia Shanti; Susi Sih Kusumawardhani (LPPM Universitas Putera Batam, 2020)
This study aims to examine the effect of 3 auditor intelligence, that is intellectual intelligence, emotional intelligence and spiritual intelligence on the accuracy of giving opinions with experience as a moderating at KAP in South Jakarta. The population in this study was the auditor at a public accounting firm in the South Jakarta area. The sampling method uses convenience sampling, based on the ease of access and availability of respondents. The number of samples 38 respondents from 5 KAP. The data analysis method uses simple linear regression and MRA. The results of the research before being moderated showed that intellectual intelligence had a significant effect on the accuracy of giving opinions. emotional intelligence does not significantly influence the accuracy of opinion giving, spiritual intelligence significantly influences the accuracy of giving opinion. Then the results of research after moderation showed that intellectual intelligence is moderated by experience does not effect the accuracy of opinion giving, emotional intelligence is moderated by experience does not effect the accuracy of opinion giving, and Spiritual intelligence moderated by experience does not effect the accuracy of opinion giving. This shows that experience cannot strengthen the effect of auditor intelligence on the accuracy of opinion giving. This shows that the experience of an auditor is not necessarily able to strengthen the auditor's decision making, especially in terms of the accuracy of opinion giving